Online Platform of Doctor Consultation on Interest in Pharmaceutical Products - Dannia Ayu Martina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Current technological developments have had an impact in the health sector, such as health consultations that can be done online via mobile phone applications or through websites. The purpose of this study was to determine the effect of the online doctor's consultation platform on interest in pharmaceutical products. The research method used is the descriptive qualitative method. The rationale for this method is used because this research wants to know about phenomena that exist in natural conditions, not under controlled, laboratory, or experimental conditions. The results showed that based on observations in the field, doctors are still a trusted source of information for the public in the process of seeking health information. Doctors are opinion leaders in terms of health and can have a large enough impact on the community to use pharmaceutical products. Many benefits can be obtained from virtual consultation services with doctors. Respondents revealed that the use of online consultations with doctors has shortened the time, schedule, or hours of consulting services that are arranged flexibly to contact doctors when needed. In addition, the responsive service makes respondents feel helpful by conducting online consultations because it does not take too long, such as waiting for an appointment to meet a doctor at a hospital. This study concludes that it is proven that after conducting health consultations in online media, all respondents stated that they were satisfied with the information provided. Furthermore, they expressed interest in conducting a further exploration of the pharmaceutical products suggested by the doctor.